Arsenic Trioxide Enhances the NK Cell Cytotoxicity Against Acute Promyelocytic Leukemia While Simultaneously Inhibiting Its Bio-Genesis - Alex, Ansu Abu; Ganesan, Saravanan; Palani, Hamenth Kumar; Balasundaram, Nithya; David, Sachin; Lakshmi, Kavitha M.; Kulkarni, Uday P.; Nisham, P. N.; Korula, Anu; Devasia, Anup J.; Janet, Nancy Beryl; Abraham, Aby; et al. (Frontiers in Immunology, 2018)
Natural Killer cells (NK) contribute significantly to eradication of cancer cells and there is increased interest in strategies to enhance it’s efficacy.Therapeutic agents used in the treatment of cancer can impact the immune system in a quantitative and qualitative manner. In this study we evaluated the impact of arsenic trioxide (ATO) used in the management of acute promyelocytic leukemia (APL) on NK cell reconstitution and function. In patients with APL treated with single agent ATO, there was a significant delay in the reconstitution of circulating NK cells to reach median normal levels from the time of diagnosis (655 days for NK cells vs 145 and 265 days for T cells and B cells respectively). In-vitro experiments demonstrated that ATO significantly reduced the CD34 hematopoietic stem cell (HSC) differentiation to NK cells. Additional experimental data demonstrate that CD34+ sorted cells when exposed to ATO lead to a significant decrease in the expression of IKZF2, ETS1 and TOX transcription factors involved in NK cell differentiation and maturation. In contrast, exposure of NK cells and leukemic cells to low doses of ATO modulates NK cell receptors and malignant cell ligand profile in a direction that enhances NK cell mediated cytolytic activity. We have demonstrated that NK cytolytic activity towards NB4 cell line when exposed to ATO was significantly higher when compared with controls. We also validated this beneficial effect in a mouse model of APL were the median survival with ATO alone and ATO+ NK was 44 days (range:33-46) vs 54 days (range:52-75). In conclusion ATO has a differential quantitative and qualitative effect on NK cell activity. This information can potentially be exploited in the management of leukemia.